2021
DOI: 10.4209/aaqr.200662
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Improvement during COVID-19 Lockdown in Bangkok Metropolitan, Thailand: Effect of the Long-range Transport of Air Pollutants

Abstract: Lockdown measures have been adopted in many countries worldwide due to the onset of the COVID-19 pandemic, including in Thailand. Air quality improvements with regard to restrictions of daily movement among Bangkok people have been reported. This study explores the impact of the COVID-19 outbreak and long-range pollution on air quality in Bangkok Metropolitan, Thailand by using ground-based and satellite measurements such as MODIS and TROPOMI data. Moreover, the results project some possible future trends of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…The COVID‐19 lockdown drastically constrained human activities on a scale larger than those campaigns, providing a good opportunity to revisit a less polluted atmosphere to understand the level of human engagement in degrading the environment and climate. This resulted in an exponential increase of COVID‐19 related studies after the outbreak, mostly focusing on the degree of air quality improvement (e.g., Dumka et al., 2021 ; Manchanda et al., 2021 ; Mishra et al., 2021 ; Misra et al., 2021 ; Wetchayont et al., 2021 ). Aerosols affect the climate by scattering and absorbing solar radiation (direct effect) (e.g., Coakley et al., 1983 ), changing the atmospheric stability and burning clouds (semi‐direct effect) (e.g., Hansen et al., 1997 ), and modifying the cloud microphysical and optical properties (indirect effect) (e.g., Albrecht, 1989 ; Twomey, 1977 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID‐19 lockdown drastically constrained human activities on a scale larger than those campaigns, providing a good opportunity to revisit a less polluted atmosphere to understand the level of human engagement in degrading the environment and climate. This resulted in an exponential increase of COVID‐19 related studies after the outbreak, mostly focusing on the degree of air quality improvement (e.g., Dumka et al., 2021 ; Manchanda et al., 2021 ; Mishra et al., 2021 ; Misra et al., 2021 ; Wetchayont et al., 2021 ). Aerosols affect the climate by scattering and absorbing solar radiation (direct effect) (e.g., Coakley et al., 1983 ), changing the atmospheric stability and burning clouds (semi‐direct effect) (e.g., Hansen et al., 1997 ), and modifying the cloud microphysical and optical properties (indirect effect) (e.g., Albrecht, 1989 ; Twomey, 1977 ).…”
Section: Introductionmentioning
confidence: 99%
“…The highest PM10-APD% values (−23%, −6%, and −10%, in June, July, and August, respectively) were found at Site 10, which is a background site, while the smallest values (up to −92% in June) were found at Site 6, which is a rural/industrial site. Wetchayont et al [32] identified a reduction in PM2.5 concentration by −15.79% in the LD period and by −23.34% in the Post-LD period by analysing measurements performed in Bangkok (Thailand) in a highly urbanized area and considering the same reference years of this study. The PM2.5 and PM10 mass concentration reductions observed in 2020 with respect to the ref-year are within the variability range evaluated by Sicard et al [31], who also considered 2017, 2018, and 2019 as reference years.…”
Section: Comparison Between Pm Mass Concentrations In 2020 and Ref-yearmentioning
confidence: 96%
“…Firstly, the statistics of Pre-LD, LD, and Post-LD periods have been compared estimating the respective mean values and the 5th, 25th, 50th, 75th, and 95th percentiles of each tested parameter that have been represented by box plots. Then, we have defined a so-called reference year (ref-year) based on measurements performed in the years 2017, 2018, and 2019, according to the selection performed in other studies [31,32]. In more detail, the daily mean values of each tested parameter referring to each of these three years have been averaged to calculate the corresponding monthly mean values of the ref-year.…”
Section: Study Area Analysed Time Intervals and Statistical Analysesmentioning
confidence: 99%
“…However, air quality did not consistently improve in China during the lockdown due to local and transboundary impacts of PM 2.5 sources ( Chang et al, 2020b ; Dai et al, 2021a ; Le et al, 2020b ), and similar cases were reported in Spain and Thailand. ( Briz et al, 2022 ; Wetchayont et al, 2021 ). These results can help understand the local and transboundary impacts of PM 2.5 sources by providing an unprecedented cross-country experiment.…”
Section: Introductionmentioning
confidence: 99%